Energy audit and optimal power supply for a commercial building in Nigeria. Issue 1 (1st January 2018) - Adewale, Adeyinka Ajao; Adekitan, Aderibigbe Israel; Idoko, Ofukowoicho Jeremiah; Agbetuyi, Felix Ayoade; Samuel, Isaac Adekunle
Abstract: Energy is indispensable to human existence, and its need is on the increase daily due to technological advancement. In recent times, there is sporadic increase in the development of modern buildings, and these buildings require a cost-effective and sustainable source of energy. Nigeria and some other African countries have major energy shortage issues due to the insufficient power generation and distribution facilities. This energy poverty creates a challenge for the growing population, and as such, it is vital to ensure that the energy supplied to a building is duly optimized and delivered cost effectively. In this study, an energy audit of an eight-floor multipurpose business complex was performed to determine the nature and type of loads within the building. Based on the load profile and energy consumption over a 10-year period, three alternative energy sources (national grid, diesel generator and photovoltaic [PV] system) were considered using various load-sharing ratios. The result reveals that though PV solar system is a renewable energy source that reduces the production of greenhouse gases generated by burning diesel, its continuous application in low–middle-income country like Nigeria may be challenged by the initial start-up capital which raises the cost of its unit energy.